Partners in research: building academic‐practice partnerships to educate and mentor advanced practice nurses. Issue 2 (1st November 2016) - Harbman, Patricia; Bryant‐Lukosius, Denise; Martin‐Misener, Ruth; Carter, Nancy; Covell, Christine L.; Donald, Faith; Gibbins, Sharyn; Kilpatrick, Kelley; McKinlay, James; Rawson, Krista; Sherifali, Diana; Tranmer, Joan; et al.
Abstract: Rationale: Clinical practice is the primary focus of advanced practice nursing (APN) roles. However, with unprecedented needs for health care reform and quality improvement (QI), health care administrators are seeking new ways to utilize all dimensions of APN expertise, especially related to research and evidence‐based practice. International studies reveal research as the most underdeveloped and underutilized aspect of these roles. Aims: To improve patient care by strengthening the capacity of advanced practice nurses to integrate research and evidence‐based practice activities into their day‐to‐day practice. Methods: An academic‐practice partnership was created among hospital‐based advanced practice nurses, nurse administrators, and APN researchers to create an innovative approach to educate and mentor advanced practice nurses in conducting point‐of‐care research, QI, or evidence‐based practice projects to improve patient, provider, and/or system outcomes. A practice‐based research course was delivered to 2 cohorts of advanced practice nurses using a range of teaching strategies including 1‐to‐1 academic mentorship. All participants completed self‐report surveys before and after course delivery. Results: Through participation in this initiative, advanced practice nurses enhanced their knowledge, skills, and confidence in the design, implementation, and/or evaluation of research, QI, and evidence‐based practice activities. Conclusion: Evaluation of this initiative provides evidence of the acceptability and feasibility of academic‐practice partnerships to educate and mentor point‐of‐care providers on how to lead, implement, and integrate research, QI and evidence‐based activities into their practices.